2020
DOI: 10.3390/foods9060696
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Consumer Preferences for Lamb Meat before and during the Economic Crisis in Spain. Analysis and Perspectives

Abstract: Determining the preferences of food consumers is key for adapting supply and demand. This adaptation of supply is dynamic rather than static, given that it develops over time and is influenced by both social and economic factors. This work presents an analysis of the development of lamb meat consumption at two points in time, 2004 and 2014, before and in the midst of the economic crisis in Spain (2007–2017). Our findings show that together with the external appearance and against the backdrop of an economic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
(80 reference statements)
1
11
0
3
Order By: Relevance
“…This study describes the novelty of the machine to escalate the productivity of roast lamb, which is not influenced in any way the origin of the meat [50], which could affect its texture or appearance when it is roasted. It is also believed that the quality of meat obtained for the experiment is consistent or standard, which is not affected by any external factors such as COVID-19, referring to a study carried out in China [51] or even any unfavourable economic landscape [52].…”
Section: Limitationsmentioning
confidence: 98%
“…This study describes the novelty of the machine to escalate the productivity of roast lamb, which is not influenced in any way the origin of the meat [50], which could affect its texture or appearance when it is roasted. It is also believed that the quality of meat obtained for the experiment is consistent or standard, which is not affected by any external factors such as COVID-19, referring to a study carried out in China [51] or even any unfavourable economic landscape [52].…”
Section: Limitationsmentioning
confidence: 98%
“…When considering lamb perception in other cultures, a wide range of attributes have been identified to be important to consumers when deciding to purchase lamb. For example, recent studies have shown that factors such as freshness, marbling, colour, the type of cut, price, and quality label are very important to lamb consumers in Brazil [ 6 ]; food safety and the absence of hormones and antibiotics are important for sheep meat consumers in Mexico [ 7 ]; and external appearance, origin, and price are important to lamb consumers in Spain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…El consumo de carne de cordero ha disminuido considerablemente en los últimos años (Rabadán et al, 2020), lo que ha provocado importantes pérdidas para el sector. Esto unido a los cambios en el tipo de alimentación de la población (comida rápida, comida preparada…) ha influido para la posible apertura de nuevos nichos de mercado para la carne de cordero.…”
Section: Introductionunclassified